2018
DOI: 10.1038/s41375-018-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow-cytometric vs. -morphologic assessment of remission in childhood acute lymphoblastic leukemia: a report from the Children’s Oncology Group (COG)

Abstract: Minimal residual disease (MRD) after initial therapy is integral to risk stratification in B- and T-precursor acute lymphoblastic leukemia (B-ALL, T-ALL). While MRD determines depth of remission, remission remains defined by morphology. We determined the outcomes of children with discordant assessments of remission by morphology vs. flow cytometry using patients age 1–30.99 years enrolled on Children’s Oncology Group ALL trials who underwent bone marrow assessment at the end of induction (N=9 350). Morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
3
30
0
6
Order By: Relevance
“…In both cases, while flow and aspirate were relatively concurrent, the biopsy was essential to determining the extent of disease involvement can be complicated by multiple factors including hypocellularity and confusion with hematogones that can be present in increased numbers in a regenerative marrow. 21,22 Additionally, these techniques lack the sensitivity of multiparametric FC to find rare, minimal levels of leukemic blasts. Combining multiple methods provides comprehensive data to more fully assess response to leukemia-directed therapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In both cases, while flow and aspirate were relatively concurrent, the biopsy was essential to determining the extent of disease involvement can be complicated by multiple factors including hypocellularity and confusion with hematogones that can be present in increased numbers in a regenerative marrow. 21,22 Additionally, these techniques lack the sensitivity of multiparametric FC to find rare, minimal levels of leukemic blasts. Combining multiple methods provides comprehensive data to more fully assess response to leukemia-directed therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Though each study provides complementary information, and in theory, a uniform assessment of disease status, we have observed numerous cases in the relapsed/refractory setting where the multiparametric FC results are discrepant from the concurrent morphologic assessment of BM aspirate and/or biopsy. Very few studies have evaluated the additive value that BM aspirate morphology 1,2 or routine BM biopsy may provide in disease assessment. 1,3 Given the prognostic role of disease detection in ALL, 4,5 having an accurate and complete assessment of disease is essential.…”
Section: Abstract Acute Lymphoblastic Leukemia Csf Minimal Rmentioning
confidence: 99%
See 2 more Smart Citations
“…found that 8030 (86%) had CNS1 disease. 17 Thus, the Australian population-based proportion of CNS1 disease, although somewhat higher, is not substantially more so than the COG experience. We do, however, acknowledge that the proportion of CNS1 in these particular COG trials is higher than that reported by other cooperative groups.…”
Section: Leukemiamentioning
confidence: 92%